Analysis of Land Reclamation Policy and Green Mining Technology on Ecosystem Stability and Mine Productivity in Kalimantan, Indonesia - Yunita Sopiana; Fildansyah, Rully; Muhtadi, Muhamad Ammar (Westscience Press, 2024)
This study examines the effects of Green Mining Technology and Land Reclamation Policy on Ecosystem Stability and Mine Productivity in Kalimantan, Indonesia. Using structural equation modeling (SEM) with Partial Least Squares (PLS), data from a sample of mining operations were analyzed to test hypotheses regarding these relationships. Results indicate significant positive relationships between both Green Mining Technology and Land Reclamation Policy with Ecosystem Stability and Mine Productivity. The findings underscore the dual benefits of sustainable practices and policy interventions in enhancing environmental sustainability and economic productivity in mining operations.